DESAIN MULTIMEDIA POWERPOINT MAHASISWA PLP PRODI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Kurnia Putri; Arza Aibonotika; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study used a qualitative descriptive method regarding two PowerPoint media designs made by PLP students at the Riau University Japanese Language Education study program which aims to explain the use of these Powerpoint media. This research is based on Richard E Mayer's theory of multimedia learning principles which are divided into seven principles: multimedia principles; the principle of spatial proximity; the principle of time proximity, the principle of coherence, modality principle, redundancy principle, and the principle of individual differences. Based on the analysis of the Powerpoint designs studied, the first data does not meet all the principles of multimedia learning because the design is only dominated by words without related images. Meanwhile, the second powerpoint media has included media elements such as words accompanied by related images, there is the addition of audio or text that is narrated. However, the design does not utilize elements of animation that can help in constructing knowledge.Key Words: Multimedia, Powerpoint, Design